Dr. S. Donald (Don) Stookey (1915–2014): Pioneering Researcher and Adventurer - Beall, George H. (Frontiers in Materials, 2016)
Don Stookey was a special person by any measure: an unassuming optimist, eminent scientist and inventor, adventurer, and a beloved family man. Don Stookey, the father of glass-ceramics, was a pioneer in inducing and understanding internal nucleation phenomena in glass. His early work on dense opal glasses and photosensitive precipitation of gold and silver in glass led to an amazing series of inventions: Fotalite®, a photosensitive opal, chemically machined Fotoform® and Fotoceram®, and TiO2-nucleated Pyroceram™ products including missile nosecones and oven-proof cookware. He received a basic patent on glass-ceramics which was contested and affirmed in court. Don was able to demonstrate a clear photochromic glass that showed reversible darkening for thousands of cycles. This material became a fixture in the ophthalmic industry. He went on to invent a full-color polychromatic glass capable of yielding a permanent patterned and monolithic stained glass. In his life outside science, Don chaired an interfaith group that founded a home for the elderly in Corning. He was also a wilderness enthusiast, surviving a plane crash in the Arctic and two boat capsizings. Even In his later years, he continued fishing off the coast of Florida and on Lake Ontario, and went solo on a trip to the Patagonian Andes.